Lrig1 Expression in Human Sebaceous Gland Tumors - Jöri Pünchera; Laurent Barnes; Gürkan Kaya (MDPI AG, 2016)
Background: Sebaceous glands contribute significantly to the barrier functions of the skin. However, little is known about their homeostasis and tumorigenesis. Recently, increased expression of stem cell marker Lrig1 has been reported in sebaceous carcinoma-like tumors of K14ΔNLef1 transgenic mice. In this study, we analyzed the Lrig1 expression in human sebaceous tumors. Methods: Twenty-eight formalin-fixed paraffin-embedded sebaceous tumor specimens (7 sebaceous hyperplasias, 7 sebaceous adenomas, 10 sebaceomas and 4 sebaceous carcinomas) were stained with anti-Lrig1, anti-CD44v3 and anti-Ki67 antibody. Results: Four (100%) sebaceous carcinomas, 8 (80%) sebaceomas, 3 (43%) sebaceous adenomas and no sebaceous hyperplasia showed Lrig1 overexpression. Discussion and Conclusion: Lrig1 is a known tumor suppressor gene and is usually considered to be an indicator of poorly aggressive tumors. In human sebaceous tumors, the stronger Lrig1 staining in sebaceous carcinoma compared to other sebaceous tumors might be a feature of an advanced stage in tumorigenesis and a bad prognosis. In our study, 100% of sebaceous carcinomas revealed Lrig1 overexpression. We propose that Lrig1 may be used as a possible new marker of poorly differentiated sebaceous carcinoma.